Gene promoter hypermethylation in leukoplakia of the oral mucosa - Mingli Liu; Lei Feng; Ximing Tang; et al (Dove Medical Press, 2010)
Mingli Liu1, Lei Feng2, Ximing Tang3, Shanchun Guo41Department of Physics, Tufts University School of Medicine, Boston, Massachussetts; 2Department of Thoracic/Head and Neck Medical Oncology, 3Biostatistics, The University of Texas MD Anderson Cancer Center, Houston, Texas; 4Sylvester Cancer Center, University of Miami School of Medicine, Florida, USAAbstract: To examine whether aberrant DNA methylation in the promoter region might occur earlier in tumorigenesis, particularly in premalignant lesions, we examined biopsies from 111 participants in a chemoprevention trial aimed at reversal of oral leukoplakia, using methylation-specific polymerase chain reaction for the promoter regions of the tumor suppressor gene CDKN2A (p16), the putative metastasis suppressor gene for death-associated protein kinase (DAP-K), the DNA repair gene O6-methyguanine-DNA-methyltransferase (MGMT), and the detoxification gene glutathione S-transferase p1(GSTP1). p16 promoter hypermethylation was detected in 21 of 82 (25.6%), DAP-K hypermethylation in 28 of 87 (32.2%), and MGMT hypermethylation in 32 of 106 (30.2%) oral leukoplakia lesions analyzed. No aberrant methylation was found at the GSTP1 gene in 110 lesions examined. Among 68 biopsies analyzed for all three genes (p16, DAP-K, MGMT), 17 biopsies were detected with an abnormal methylation pattern at only one gene, 15 at two genes, and 8 at all three genes. Among clinical characteristics and their correlation with methylation, only alcohol consumption was correlated with DAP-K methylation (P = 0.027), while MGMT methylation was more frequent in females (P = 0.003) and nonsmokers (P = 0.0005). A significant correlation was found between p16 and DAP-K hypermethylation; p16 promoter was methylated in 14 (56%) of 25 lesions with DAP-K methylation, and only 5 (11.1%) of 45 DAP-K methylation-negative lesions (P = 0.0001). DAP-K aberrant methylation was also significantly correlated with MGMT methylation (16 of 31 in MGMT methylation-positive lesions versus 12 of 52 MGMT methylation-negative lesions, P = 0.0016). Our results suggest that epigenetic mechanisms of inactivation, such as aberrant methylation of p16, DAP-K, and MGMT genes, occur early in head and neck tumorigenesis, and might play a role in the progression of these lesions.Keywords: p16, DAP-K, MGMT, GSTP1 genes, methylation, leukoplakia